Towards a Better and Harmonized Education in Antimicrobial Stewardship in European Veterinary Curricula - Carmen Espinosa-Gongora; Lisbeth Rem Jessen; Oliver James Dyar; Alain Bousquet-Melou; Bruno González-Zorn; Céline Pulcini; Giovanni Re; Stefan Schwarz; Dorina Timofte; Pierre-Louis Toutain; Luca Guardabassi; The PREPARE-VET Working Group; et al. (MDPI AG, 2021)
Education in antimicrobial stewardship (AMS) in veterinary medicine is essential to foster responsible antimicrobial use and control of antimicrobial resistance (AMR) in animals. AMS is listed by the EU and international organizations among the basic 'Day One Competences' required of veterinary students upon graduation. Our aim was to evaluate the quality of education of European veterinary students in AMS. We distributed a 27-item survey addressing the perceptions of preparedness and acquired skills on key topics related to AMS to final-year veterinary students in Europe. We collected 3423 complete answers from 89 veterinary schools in 30 countries. Selection of treatment strategies and awareness of emerging AMR problems were markedly different between countries. Overall, only one in four students was familiar with guidelines for antimicrobial use. The students perceived a medium-high impact of veterinary antimicrobial use on AMR in humans. Notably, 75% of the students felt the need for improved teaching on AMS, half of which also demanded more teaching on general antimicrobial therapy. Our results highlight several possible strategies to improve the quality of education, ranging from a better link between clinical rotations and the theory taught in pre-clinical modules, to a more effective introduction into best practices for antimicrobial use.